Source mechanisms of earthquakes theory and practice - Udías Vallina, Agustín (Cambridge University Press, 2014)
This book presents an innovative new approach to studying source mechanisms of earthquakes, combining theory and observation in a unified methodology, with a key focus on the mechanics governing fault failures. It explains source mechanisms by building from fundamental concepts such as the equations of elasticity theory to more advanced problems including dislocation theory, kinematic models and fracture dynamics. The theory is presented first in student-friendly form using consistent notation throughout, and with full, detailed mathematical derivations that enable students to follow each step. Later chapters explain the widely-used practical modelling methods for source mechanism determination, linking clearly to the theoretical foundations, and highlighting the processing of digital seismological data. Providing a unique balance between application techniques and theory, this is an ideal guide for graduate students and researchers in seismology, tectonophysics, geodynamics and geomechanics, and a valuable practical resource for professionals working in seismic hazard assessment and seismic engineering.